Shaping Pious Children Through Islamic Religious Education in Early Childhood - Cintya Warda Ningsih (Yayasan Bayt Shufiya Nusantara, 2023)
This study aims to explore the role and support of parents in instilling Islamic religious education from an early age. The research method used is quantitative with research instruments using the Likert scale. The sample used consisted of 100 children aged 5 to 10 years from Paya Bomban Hamlet, Pasir Tuntung Village, South Labuhan Batu Regency. This research is estimated to take place from February to June 2024. The results of the study show that the success of parents in instilling Islamic religious education in children is inseparable from the role and responsibility of parents at home. In addition to being the first madrasah for children, parents also play a role in directing children to learn Islam more deeply through education in madrasah schools, while maintaining an environment that supports Islamic religious learning. Therefore, the synergy between parental support and educational institutions is an important factor in instilling Islamic religious education in children from an early age.